If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying K(k + 4) = 0 Reorder the terms: K(4 + k) = 0 (4 * K + k * K) = 0 (4K + kK) = 0 Solving 4K + kK = 0 Solving for variable 'K'. Move all terms containing K to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'K'. K(4 + k) = 0Subproblem 1
Set the factor 'K' equal to zero and attempt to solve: Simplifying K = 0 Solving K = 0 Move all terms containing K to the left, all other terms to the right. Simplifying K = 0Subproblem 2
Set the factor '(4 + k)' equal to zero and attempt to solve: Simplifying 4 + k = 0 Solving 4 + k = 0 Move all terms containing K to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + k = 0 + -4 Combine like terms: 4 + -4 = 0 0 + k = 0 + -4 k = 0 + -4 Combine like terms: 0 + -4 = -4 k = -4 Add '-1k' to each side of the equation. k + -1k = -4 + -1k Combine like terms: k + -1k = 0 0 = -4 + -1k Simplifying 0 = -4 + -1k The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
K = {0}
| 3(30+s)=4(s+1s) | | 13x-1=x+27 | | 5/3x:3/1 | | -9(x+3)+4x+5=6x+12 | | 8(31.25+-0.5y)+4y=250 | | 3(30+s)=4(s+1a) | | 2w+6=30 | | 2m+1=6m+2 | | 8(31.25+-0.5)+4y=250 | | x^4+6x^2+2x=0 | | 21m+36=3m | | 14x-21=49 | | (1/6x-5)-(6/5-6x) | | 8(x-9)=12 | | -3.4=.4j | | 49=25/1y | | 7c-7b=x | | 3(x+7)-4(x+3)=10 | | 12+50=949.88 | | 6y+(-4)= | | -2x=5x-9x+16-10 | | 7=.75*20+4 | | -3/4*8 | | 3+66x=33x+22 | | -x/4=-22 | | 4(7x+1)=312 | | .6h=1.8 | | 2(3y-6)= | | 8x+3y=101 | | -4(8+5x)=-32 | | 14=4a+2 | | 5x+11=7-2x |